Reflex - Akinyemi, Rowena (Oxford bookworms library, 2000)
"People who ride racehorses love the speed, the excitement, the danger -and winning the race. Philip Nore has been riding for many years and he always wants to win -but sometimes he is told to lose. Why? And what us the mystery about the photographer, George Millace, who has just died in a car crash? Philip Nore knows the answer to the second. But as he begins to learn George Millace's secrets, he realizes that his own life is in danger" --contratapa.